Revenues and expenditures of the municipal budget ("Journal "U". Economy. Management. Finance.", 2023)
This article is devoted to the analysis of the composition of revenues and the implementation of expenditures of the municipal district budget.
Keywords: territory of the municipality; budget; budget revenues; budget expenditures